STRATEGI OPTIMASI BIAYA PEMELIHARAAN JALAN BERBASIS KINERJA DAN ANALISIS SIKLUS HIDUP (STUDI KASUS: JALAN PANGERAN TIRTAYASA, BANDAR LAMPUNG) - Simanjuntak, Indi Rezki Uli (Nusantara Hasana Journal, 2025)
The condition of Pangeran Tirtayasa Road, with a PCI score of 47.04, serves as the background for this paper. This figure indicates the need for an effective maintenance strategy within a limited budget. This limited budget prompted the idea of conducting a performance-based cost optimization study by comparing maintenance alternatives using life cycle cost analysis (LCCA) and the integration of International Roughness Index (IRI) parameters for damage prediction. The method used was secondary PCI data from a survey by Muhammad Zaid (2021), processed with segment homogenization (AASHTO CDA). Two maintenance scenarios (IRI-based and PCI-based) were compared using LCCA with inflation at 2.65% and an interest rate of 4.51%. The results showed that alternative 1 (IRI-based) was more economical (Rp1.03 billion vs. Rp1.61 billion) with a service life of 35 years. This can be recommended by prioritizing routine maintenance (years 4, 6, and 8) and non-structural overlays (year 17).